Targeted Therapy: Attacking Cancer with Molecular and Immunological Targeted Agents - Wilkes, Gail (Asia-Pacific journal of oncology nursing, 2018)
Today, personalized cancer therapy with targeted agents has taken center stage, and offers individualized treatment to many. As the mysteries of the genes in a cell's DNA and their specific proteins are defined, advances in the understanding of cancer gene mutations and how cancer evades the immune system have been made. This article provides a basic and simplified understanding of the available (Food and Drug Administration- approved) molecularly and immunologically targeted agents in the USA. Other agents may be available in Asia, and throughout the USA and the world, many more agents are being studied. Nursing implications for drug classes are reviewed.